Some Dare Call it Leadership: A Review of Leadership in Spaces and Places - Peltonen, Tuomo (Organizational Aesthetics, 2014)
Leadership in Spaces and Places is a captivating visual (re)presentation about the ways in which different spaces of work, performance and action are being organized by and organize actors, scripts and patterns in the social realms. It features short non-narrated scenes from a number of organizational and non- organizational contexts, ranging from corporate offices to decayed villas to a historical dry dock to a funeral chapel to a theatre to a kids' bedroom. The film is mainly shot using the conventional "human eye" angle on the subjects and objects of interest. In some instances, a slight camera run is used to add a feeling of naturalistic motion to the illustrated meaning of space. However, there seems to be no explicit attempt to set into the "user's position" by imitating the perspective of an employee or customer living and acting in the structures of the space. Especially in the corporate offices it would have been interesting to get a feeling of how the users appropriate and adapt the open space design in their own routines and movements. The film is composed of a number of scenes that explore the spatial structures and meanings in a particular domain or place. The order and succession of the scenes does not become univocally clear from the totality, and the viewer is left on his or her own devices to make more analytic interpretations from the comparison of different scenes. Maybe a more limited number of extensive case studies could have been easier from a reception point of view as now there is a lot of implicit stimuli made available for the viewer to build his or her own conceptual reflection on the lessons learned from the scenes. One such possibly idiosyncratic reading of the film points to the differences between the rather naive romanticism of the "open space" projects of the corporate actors and the slightly more realistic views and practices of the non-organizational places - the latter acknowledging the reciprocal relation between the humans and the material structures and intending to create emotionally and practically intelligent designs that navigate between the dualism of rationally imposed forms and freely emerging configurations of spatial meanings. As it happens, there was a lot of stuff in the video that was familiar to me personally. Yet what the film undeniably managed to accomplish is the opportunity to have a fresh look into the seeming everydayness of the physical and architectural textures of our organizational spaces and places. I think after seeing the film, the attitude of the viewer towards the material surroundings of his or her social and organizational life is prone to change. We then see spaces with a heightened clarity and rigor, but - despite the new reflexivity - the architectural spaces and their material forms continue to offer themselves to us as guides and reminders of how we are and what we need to do. This messy dynamics could be termed a heterogeneous process of organizing, and some dare to call it leadership.